Green valorization of defatted rice bran: unlocking bioactive and prebiotic potential using deep eutectic solvent extraction - Sombutsuwan, Piraporn; Puputtrarakra, Chutima; Whangsomnuek, Nattawut; Nakornsadet, Akkaradech; Chumsantea, Salisa; Aryusuk, Kornkanok Aryusuk; Chunglok, Wilanee (Agriculture and Natural Resources, 2026)
Importance of the work: Defatted rice bran (DFRB), a nutrient-rich byproduct of rice oil extraction, is often discarded as waste. Utilizing a sustainable and eco-friendly extraction method can help to unlock its potential for applications in functional foods, nutraceuticals and agriculture. This study explored the use of deep eutectic solvents (DES) as a green extraction technology to recover bioactive and prebiotic compounds from DFRB. Objectives: To extract bioactive compounds from DFRB using a sodium propionate/glycerol (Na:Gly) DES and to evaluate their phenolic composition, antioxidant activity and prebiotic properties. Materials and Methods: DFRB was extracted using Na:Gly DES (1:8, weight per volume) at 70°C for 5 hr. The extract was analyzed for its phenolic content, phenolic composition, protein, reducing sugars and phytic acid. Its antioxidant activity was assessed using 2,2-diphenyl-1-picrylhydrazyl and 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid assays, while its prebiotic potential was tested based on monitoring L. plantarum growth. In addition, the extract’s ability to inhibit harmful bacteria was evaluated. Results: The extraction method recovered a substantial proportion of glycosylated (47.09%) , esterified (45.26%) and free phenolic (7.65%) compounds, with ferulic acid, p-coumaric acid and sinapic acid as the dominant phenolic acids. In addition, the extract contained 7.08 mg/g of protein, 4.26 mg/g of reducing sugars and 1.14 mg/g of phytic acid. The carbon and nitrogen sources in the DFRB extract were suitable for the growth of L. plantarum, while the phenolic acids inhibited the growth of S. aureus and P. aeruginosa. Main finding: Applying Na:Gly DES was an effective, sustainable and eco-friendly method for extracting valuable bioactive compounds from DFRB. These findings support its potential use in functional foods, gut health applications and sustainable agriculture.